BMI is associated with sperm quality and sex hormones in men: a meta-analysis - Ji, Fengming; Yan, Bing; Zhanghuang, Chenghao; Wu, Chengchuang; Dai, Jinshuan; Wu, Shengde (Frontiers in Endocrinology, 2025)
AimTo systematically evaluate the relationship between body mass index (BMI) and sperm quality parameters as well as sex hormones levels in males.MethodA comprehensive literature search was conducted across Pubmed, Embase and the Cochrane Library for literature, China National Knowledge Infrastructure, and Wanfang database. Studies investigating the association between BMI and semen parameters or sex hormones in adult males (>18 years) were included. Two reviewers independently performed study selection, data extraction, and quality evaluation Meta-analysis was performed using RevMan 5.4 and Stata 18.0.ResultsOf the 275 studies identified, 14 met the inclusion criteria. A total of 14 studies involving 8443 patients were included, including 3467 cases of normal BMI, 3444 cases of overweight and 1532 cases were obesity. All 14 studies involved sperm quality analysis, and 4 studies addressed sex hormone analysis. The meta-analysis results indicate that there were statistically significant differences in normal morphology (NM), total motility (TM), sperm concentration (SC), progressive motility (PM), volume and total sperm count (TSC) among the three groups. In the analysis of sex hormones, total testosterone (TT), follicle stimulating hormone (FSH) and luteinizing hormone (LH) showed statistically significant difference among three groups.ConclusionElevated BMI is significantly associated with impaired sperm quality and altered sex hormone levels. BMI should be considered a risk factor in male fertility assessments. Further longitudinal studies are needed to explore the reversibility of these effects through lifestyle interventions.